FORMATION OF USERS INFORMATION CULTURE IN SCIENTIFIC AND TECHNICAL LIBRARY OF NATIONAL MINING UNIVERSITY - Lozdan, Larysa V. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The paper observes the role of library and all its departments in formation of user information literacy through the creation of common information and communication university space.